Reaction of traditional rainfed rice accessions to brown spot, blast and sheath rot diseases - D. MAITI, V.S. CHAUHAN; J.B. TOMAR, V.D. SHUKLA, J.S. CHAUHAN, M. VARIAR (Indian Phytopathology, 2002)
Accessions (183) from diverse geographical areas of the plateau region of Bihar and adjoining parts of West Bengal, India, were evaluated for resistance to leaf blast (Pyricularia oryzae [Magnaporthe grisea]), brown spot (Helminthosporium oryzae [Cochliobolus miyabeanus]) and sheath rot (Sarocladium oryzae), the major diseases of the uplands of this region during 1990-93. Each accession was tested for a minimum of 2 seasons. The collection proved to be a good source of resistance genes for the management of brown spot and sheath rot. Fifty-three accessions were resistant (score _3) for brown spot. Most accessions showed fairly high tolerance of sheath rot. All the collections were susceptible to blast. Thirty-two accessions with multiple resistance/tolerance were identified.